Urban-Rural Disparities in Depressive Symptoms Among Employed Individual: Education Plays an Important Role - Xie C; Zhao Z; Gao L; Yuan L; Liu L (Psychology Research and Behavior Management)
Congshang Xie,* Zhe Zhao,* Lei Gao,* Lei Yuan, Lijuan Liu Department of Health Management, Faculty of Military Health Service, Naval Medical University, Shanghai, 200433, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lijuan Liu, Email liulijuan79@sina.com; Lei Yuan, Email yuanleigz@163.comObjective: Focusing on the relationship between education level and the occurrence of depressive symptoms, the purpose of this study was to investigate the factors influencing urban-rural differences in depressive symptoms among employed Chinese workers and to measure the contribution of relevant influencing factors.Measurements: This study utilized the nationally representative resampled data from the China Family Panel Studies (CFPS) in 2018. A binary logistic regression model was established to explore the major factors influencing depressive symptoms among employed individuals. The Fairlie decomposition method was employed to investigate the impact of education level and other influencing factors on the urban-rural differences in the occurrence of depressive symptoms.Results: The proportion of depressive symptoms among employed persons in China was 14.51%. The results showed that the proportion of depressive symptoms was higher among rural workers (17.09%) than urban workers (11.75%). The Fairlie model was developed with 65.70% explanatory power, and the differences in depressive symptoms between urban and rural employed persons were mainly related to literacy (39.10%), self-rated health (12.39%), life satisfaction (8.36%), job satisfaction (7.60%), marital status (− 4.96%), gender (− 3.61%), chronic disease status (2.99%) and BMI (1.41%) were related.Conclusion: This study found that the prevalence of depressive symptoms was higher among rural employed persons than among urban employed persons, which was mainly related to the differences between urban and rural residents in factors such as education level, health status and marital status. The Chinese government should pay more attention to the mental health of the working population and take measures to reduce the differences in depressive symptoms between urban and rural areas in China.Keywords: employed person, rural-urban differences, influencing factor, depressive symptoms, decomposition analysis